Deep Learning-Based Teaching Strategies of Ideological and Political Courses Under the Background of Educational Psychology - He, Xiaoqing; Chen, Peiyao; Wu, Jieting; Dong, Zhen (Frontiers in Psychology, 2021)
At present, the low teaching efficiency has been the common problem of ideological and political education in colleges and universities in China. It is essential to improve the teaching efficiency and realize the intelligent information transformation of ideological and political courses of colleges and universities. First, the relationship between college students’ ideological and political courses and educational psychology is analyzed based on the theoretical characteristics of educational psychology and college ideological and political courses. Besides, the teaching efficiency of ideological and political courses based on DL (deep learning) is analyzed through literature survey. Combined with online teaching modes such as Flipped Classroom and Massive Open Online Courses, a comprehensive online teaching mode of college ideological and political courses is proposed via educational psychology and Single Shot MutiBox Detectior networks of DL. Then, a total of 100 research objects are selected randomly from the freshmen and sophomores in Southwest University of Science and Technology, and the acceptability to the online ideological and political courses of students is analyzed by questionnaire survey. The results show that the adopted questionnaire has high reliability and validity, and the proportion of respondents of different genders, grades, and majors is essentially balanced. More than half of the students have a good understanding of the comprehensive ideological and political course, and make a progress in values, ideology, moral, and knowledge reserves. More than half of the students have a positive attitude to the course, and they think that the class atmosphere of the course is active, which is conducive to a satisfactory learning effect. This indicates that the teaching strategy of ideological and political courses in colleges and universities that integrates educational psychology, DL, and online information can attract students. The contribution of this study is that the research outcome can be applied to the concrete formulation of teaching strategies of ideological and political courses for college students.